If it's not what You are looking for type in the equation solver your own equation and let us solve it.
x in (-oo:+oo)
(3/4)*x-((1/3)*x) = 6 // - 6
(3/4)*x-((1/3)*x)-6 = 0
(3/4)*x+(-1/3)*x-6 = 0
5/12*x-6 = 0 // + 6
5/12*x = 6 // : 5/12
x = 6/5/12
x = 72/5
x = 72/5
| 4-2x=-2+4x | | 3(r-13)=12 | | 5z=z+4 | | 2x=40-3y | | 9a+27=30a | | 11=2q+7 | | -6(-2N-9)=-5(4N-10) | | 360=z+74+78+55 | | 9=8x+x | | y-4=-3(-5)+2 | | 240-x=125 | | 0=z^2-26z+100 | | 6v-v=25 | | 8+4(2x+10)=24 | | 9/26=n/52 | | y=3x^2-30x+69 | | 3n+23=36 | | (5/2)(4x-8)-2(6x-7)=-10 | | 3x+5x-15=6x-1 | | 360=z+55+78+74 | | 25/4=n/12 | | 15x+3=15x-10 | | x^2+10x=4x^2-8 | | 360=2+55+78+74 | | 3b*7n= | | 3x+5x-15=6sx-1 | | 40=((x-0.1)/x)*100 | | x^5-6x^3+9t=0 | | x+1=3x-8 | | x^2+10=4x^2-8 | | 4x-y+15=0 | | 17-k=2 |